2017
DOI: 10.1101/cshperspect.a033274
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Family Signaling in Early Vertebrate Development

Abstract: TGF-β family ligands function in inducing and patterning many tissues of the early vertebrate embryonic body plan. Nodal signaling is essential for the specification of mesendodermal tissues and the concurrent cellular movements of gastrulation. Bone morphogenetic protein (BMP) signaling patterns tissues along the dorsal-ventral axis and simultaneously directs the cell movements of convergence and extension. After gastrulation, a second wave of Nodal signaling breaks the symmetry between the left and right sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
122
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 812 publications
(1,441 reference statements)
5
122
0
4
Order By: Relevance
“…Nodal and BMP4 are morphogens crucial for gastrulation in vertebrates 13 . Each pathway has distinct receptor complexes that phosphorylate specific signal transducers, known as receptor-Smads, which then complex with the shared cofactor Smad4 to activate target genes 14 . Here we show in human embryonic stem cells (hESCs) that the response to BMP4 signaling indeed is determined by the ligand concentration, but that unexpectedly, the expression of many mesodermal targets of Activin/Nodal depends on rate of concentration increase.…”
mentioning
confidence: 99%
“…Nodal and BMP4 are morphogens crucial for gastrulation in vertebrates 13 . Each pathway has distinct receptor complexes that phosphorylate specific signal transducers, known as receptor-Smads, which then complex with the shared cofactor Smad4 to activate target genes 14 . Here we show in human embryonic stem cells (hESCs) that the response to BMP4 signaling indeed is determined by the ligand concentration, but that unexpectedly, the expression of many mesodermal targets of Activin/Nodal depends on rate of concentration increase.…”
mentioning
confidence: 99%
“…[10][11][12][13] The controls involve transcriptional autoregulation and synexpression, as well as feed-forward or feedback mechanisms, acting on the transcription of the signaling system components. [14][15][16][17][18][19] Altogether, this mounts the appropriate transcriptional response in target cells, [20][21][22] which is crucial for embryogenesis, tissue/organ formation and, in the adult, repair after injury. [23][24][25][26][27] Despite significant efforts in identifying and experimentally addressing these regulatory mechanisms, an integrated understanding of the transcriptional dynamics of the TGFβ-family system, and their gene-gene interactions, as a whole is not readily available.…”
Section: Neuronal) Cellsmentioning
confidence: 99%
“…It is a single‐copy gene in most animal groups, but in vertebrates, it has a paralog called Nodal‐related. The Nodal pathway is active during the pregastrulation and gastrulation stages of development (Shen, ; Zinski, Tajer, & Mullins, ) and is responsible for multiple fundamental processes such as mesoderm induction and patterning, endoderm function, neural patterning, establishment of left‐right asymmetry, dorsal‐ventral axis specification, anterior–posterior axis formation, and maintenance of undifferentiated embryonic stem cells (Conlon, Lyons, Takaesu, Barth, & Kispert, ; Feldman et al, ; Jones et al, ; Schier, ; Shen, ). Recently, three independent groups have shown that in vertebrates Nodal needs to form heterodimers with the GDF1/3 protein, encoded by another member of the TGF‐β superfamily, to activate the signaling pathway (Bisgrove, Su, & Yost, ; Montague & Schier, ; Pelliccia, Jindal, & Burdine, ).…”
Section: Introductionmentioning
confidence: 99%